1994
DOI: 10.1149/1.2059270
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Properties of Organic Liquid Electrolytes Based on Quaternary Onium Salts for Electrical Double‐Layer Capacitors

Abstract: The electrolytic conductivities and limiting reduction and oxidation potentials for various organic liquid electrolytes based on quaternary onium salts have been measured to find better electrolytes for electrical double-layer capacitors. An electrolyte composed of tetraethylammonium cation, tetrafluoroborate anion, and propylene carbonate solvent showed well-balanced performance of high electrolytic conductivity, a wide stable potential window and resistance to hydrolysis. Among quaternary onium salts, trieth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
222
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(244 citation statements)
references
References 2 publications
11
222
3
Order By: Relevance
“…The selection of the lithium salt, in conjunction with the PC solvent, offered a particularly low conductivity since lithium salts typically afford 2-4× lower conductivities than quaternary ammonium salts, regardless of the solvent. 46 Table I quantifies the conductivities and viscosities of the 4 different redox active electrolyte compositions investigated, where 0.5 M TEATFSI in MeCN serves as a low viscosity and high conductivity supporting electrolyte and 0.5 M LiTFSI in PC serves as a high viscosity and low conductivity supporting electrolyte. Additionally, a prior study has reported the conductivity of dry SGL 25AA carbon paper, under 20% compression, to be 2200-2700 mS cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The selection of the lithium salt, in conjunction with the PC solvent, offered a particularly low conductivity since lithium salts typically afford 2-4× lower conductivities than quaternary ammonium salts, regardless of the solvent. 46 Table I quantifies the conductivities and viscosities of the 4 different redox active electrolyte compositions investigated, where 0.5 M TEATFSI in MeCN serves as a low viscosity and high conductivity supporting electrolyte and 0.5 M LiTFSI in PC serves as a high viscosity and low conductivity supporting electrolyte. Additionally, a prior study has reported the conductivity of dry SGL 25AA carbon paper, under 20% compression, to be 2200-2700 mS cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Although five isomers are conceivable, only three could be unambigu- Ref. [22] ously identified via 11 B NMR. The chemical shifts of the different isomers are very similar and the corresponding signals overlapping.…”
Section: Resultsmentioning
confidence: 99%
“…depending on the length of the alkyl chains) [22]. The conductivity of 1 M solutions of the azolylborate salts in acetonitrile is summarized in Table 2 and compared to 1 M TEABF.…”
Section: Resultsmentioning
confidence: 99%
“…This quantity depends strongly on the electrolyte conductivity and its viscosity. Based on the experimental investigations reported in [16][17][18] the dependency of the electrolyte conductivity k as a function of its temperature can be described by the following equation:…”
Section: Sc Ageing Processes Description At Macroscopic Levelmentioning
confidence: 99%